A Study of Blended Learning in Higher Learning Education: Implementation and Challenges in 21st Century - Sam, Man Keong; Soong, Cai Juan (INTI International University, 2019)
With the advent of the new millennium, the challenge for higher learning education is to meet the needs of students in the 21st century. Millennials are hailed as the most technically savvy students of this century, forcing educators to study new teaching methods that combine technology use. To meet these needs, new teaching approaches such as blended learning become a viable alternative to traditional teaching approach. In addition, we as educators urge to explore the new approach to improve our teaching and learning skills. Nevertheless, adopting a new teaching approach is always a dispiriting and challenge task in an early-adopted stage with limited resource circumstances. Even though many educational institutes favour blended learning over traditional approach, but yet some academicians are still apprehensive about teaching in blended learning. Hence, a study has been conducted to investigate the various challenges in the implementation of blended learning in delivering technical modules in higher learning institutions. A pilot test of blended learning is carry out in this study. Data are collected from instructors via questionnaire survey. Data collected are analysed using both descriptive statistics and statistical tests to determine the major challenges. Thus, based on this premise, it convinced us that these crucial information can be right guidance and assistance to unlock frontiers for preparing educators in 21st century in tertiary university.